2021
DOI: 10.3390/jcm10020221
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Mechanisms for Hepatocellular Carcinoma Risk after Direct-Acting Antiviral Treatment of Hepatitis C Virus Infection

Abstract: Direct-acting antiviral agents (DAAs) that allow for rapid clearance of hepatitis C virus (HCV) may evoke immunological changes. Some cases of rapid de novo hepatocellular carcinoma (HCC) development or early recurrence of HCC after DAA treatment have been reported. During chronic HCV infection, natural killer (NK) cells exhibited a deviant functional phenotype with decreased production of antiviral cytokines and increased cytotoxicity; however, DAA treatment rapidly decreased their cytotoxic function. Effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 110 publications
(156 reference statements)
0
12
0
Order By: Relevance
“…The incidence of primary liver cancer is largely explained by infection with hepatitis B and C viruses, and such infections account for over 80% of liver cancer cases worldwide (6). In fact, numerous studies have demonstrated a strong correlation between chronic viral hepatitis, particularly hepatitis induced by hepatitis B and C viruses and liver cancer development (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of primary liver cancer is largely explained by infection with hepatitis B and C viruses, and such infections account for over 80% of liver cancer cases worldwide (6). In fact, numerous studies have demonstrated a strong correlation between chronic viral hepatitis, particularly hepatitis induced by hepatitis B and C viruses and liver cancer development (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Two identified subgroups are PD-1 + TCF1 + cells, capable of self-regeneration, and terminally exhausted PD-1 + TCF1 − cells. [19][20][21] The response to anti-PD-1 improves when PD-1 + TCF1 + cells are dominant, but not when the terminally exhausted PD-1 + TCF1 − T cells replace their precursors in the TME. [19][20][21] Multiplex immunohistochemistry and gene expression assays of 919 regions of 158 HCC tissues revealed that the immune microenvironment in HCC is heterogeneous and can be classified into three different subtypes: immune-high, -mid, and -low.…”
Section: Immunological Heterogeneity Of Hccmentioning
confidence: 99%
“…changes the phenotype of infected hepatocytes and intrahepatic monocytes/macrophages while contributing to HCC. 20,104,105 The inflammatory activity of intrahepatic macrophages, which is closely associated with mucosalassociated invariant T (MAIT) cell activity, is markedly attenuated after rapid viral clearance by DAAs. 106 MAIT cells are activated by IL-12, IL-15, and IL-18, which are usually produced by activated macrophages/monocytes.…”
Section: In Chronic Hepatitis C Virus (Hcv) Infection Rapid Viral Eradication By Direct-acting Antivirals (Daas)mentioning
confidence: 99%
“…The deadly disease leads to individual liver problems, around 350,000 individuals' yearly loss of their lives around the globe [4]. There are various treatments to cure hepatitis, out of which antiviral medicine can treat 95% of the patients successfully [5,6].…”
Section: Introductionmentioning
confidence: 99%